THE INFLUENCE OF WOMEN'S LEADERSHIP AND ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF BOARD OF MANAGEMENT IN PARTI AMANAT NASIONAL WEST JAVA REGION - YOSEPH MAHDI YUNANSYAH; DARMO. H. SUWIRYO; SAKTI ALAMSYAH (CV KULTURA DIGITAL MEDIA, 2023)
The focus of this research is to evaluate the extent to which the influence of women's leadership, either partially or simultaneously, has on organizational culture in DPW PAN of West Java. The research method used in this study is a quantitative method using survey techniques. For data collection, questionnaires were used to be given to respondents (staff) with a total population of 45 respondents. For data analysis, multiple linear regression analysis and path analysis were used. The hypothesis used is SPSS Version 23.0 (Statistical Package For The Social Sciences). Based on the results of the research that has been analyzed, there is a significant and positive influence of women's leadership and organizational culture on the overall organizational culture. The contribution of these two factors reached 36.3%, while the remaining 63.7% was influenced by other factors which were not the focus of the research. It can be concluded that all the observed coefficients have a fairly high level of significance.